Plasticity of the hypocretinergic/orexinergic system after a chronic treatment with suvorexant in rats. Role of the hypocretinergic/orexinergic receptor 1 as an autoreceptor - Carrera-Cañas, Carlos; de Andrés, Isabel; Callejo, Marta; Garzón, Miguel (Frontiers in Molecular Neuroscience, 2022)
The hypothalamic hypocretinergic/orexinergic (Hcrt/Ox) system is involved in many physiological and pathophysiological processes. Malfunction of Hcrt/Ox transmission results in narcolepsy, a sleep disease caused in humans by progressive neurodegeneration of hypothalamic neurons containing Hcrt/Ox. To explore the plasticity of the Hcrt/Ox system, we systemically administered suvorexant (a dual Hcrt/Ox receptor antagonist) in rats to chronically block Hcrt/Ox transmission without damaging Hcrt/Ox cells. Three groups of 8 rats (4 males and 4 females) received daily i.p. injections of suvorexant (10 or 30mg/kg) or vehicle (DMSO) over a period of 7 days in which the body weight was monitored. After the treatments cerebrospinal fluid (CSF) Hcrt1/OxA concentration was measured by ELISA, and hypothalamic Hcrt/OxR1 and Hcrt/OxR2 levels by western blot. The systemic blockade of the Hcrt/Ox transmission with the high dose of suvorexant produced a significant increase in the body weight at the end of the treatment, and a significant decrease in CSF Hcrt1/OxA levels, both features typical in human narcolepsy type 1. Besides, a significant overexpression of Hcrt/OxR1 in the hypothalamus without significant changes in Hcrt/OxR2 also occurred. For the different molecular indices analyzed here, there were not statistically significant changes in relation with the sex factor. Only the interaction “treatment x sex” resulted statistically significant for the hypothalamic Hcrt/OxR1 levels. The homeostatic changes observed in the Hcrt/Ox system after the chronic blockade of its transmission -decrease in CSF Hcrt1/OXA levels and overexpression of hypothalamic Hcrt/OxR1- support an autoregulatory role of Hcrt/OxR1 within the hypothalamus, which would induce the synthesis/release of Hcrt/Ox, but also decrease its availability at the plasma membrane after binding Hcrt1/OxA.